Levels of zinc and lipid peroxidation in acute coronary syndrome - Cikim, G; Canatan, H; Gursu, MF; Gulcu, F; Baydas, G; Kilicoglu, AE (Humana Press Inc, 2003)
The present study was carried out on 20 female patients diagnosed with acute coronary syndrome (ACS). The control group was composed of 20 healthy female volunteers. Plasma malondialdehyde (MDA) levels and serum zinc (Zn), total cholesterol, low-density lipoprotein (LDL) cholesterol, high-density lipoprotein (HDL) cholesterol, and VLDL-cholesterol, Lp(a), Apo-A(1), and Apo-B were determined in all patients and controls. Plasma MDA levels were determined to be significantly high in patients with ACS compared to the controls (1.75+/-0.27 vs 0.8+/-0.43 nmol/mL; p<0.05). On the other hand, Zn levels in patients with ACS were determined to be significantly low compared to the control group (67.9+/-14.8 vs 101.8+/-22.4 mg/dL; p<0.05). There was a statistically significant negative correlation between MDA and Zn levels in patients with ACS (r = -0.678, p<0.05). Other lipid parameters were significantly altered in patients with ACS compared to the controls (p<0.05). In conclusion, Zn and lipid peroxidation levels are important in patients with ACS and they must be monitored during diagnosis and treatment of these patients.
Keywords: acute coronary syndrome; lipid peroxidation; MDA; zinc